Islet Autoimmunity in Adults With Impaired Glucose Tolerance and Recently Diagnosed, Treatment Naïve Type 2 Diabetes in the Restoring Insulin SEcretion (RISE) Study - Brooks-Worrell, Barbara M.; Tjaden, Ashley H.; Edelstein, Sharon L.; Palomino, Brenda; Utzschneider, Kristina M.; Arslanian, Silva; Mather, Kieren J.; Buchanan, Thomas A.; Nadeau, Kristen J.; Atkinson, Karen; Barengolts, Elena; Kahn, Steven E.; et al. (Frontiers in Immunology, 2021)
The presence of islet autoantibodies and islet reactive T cells (T+) in adults with established type 2 diabetes (T2D) have been shown to identify those patients with more severe beta-cell dysfunction. However, at what stage in the progression toward clinical T2D does islet autoimmunity emerge as an important component influencing beta-cell dysfunction? In this ancillary study to the Restoring Insulin SEcretion (RISE) Study, we investigated the prevalence of and association with beta-cell dysfunction of T+ and autoantibodies to the 65 kDa glutamic acid decarboxylase antigen (GADA) in obese pre-diabetes adults with impaired glucose tolerance (IGT) and recently diagnosed treatment naïve (Ndx) T2D. We further investigated the effect of 12 months of RISE interventions (metformin or liraglutide plus metformin, or with 3 months of insulin glargine followed by 9 months of metformin or placebo) on islet autoimmune reactivity. We observed GADA(+) in 1.6% of NdxT2D and 4.6% of IGT at baseline, and in 1.6% of NdxT2D and 5.3% of IGT at 12 months, but no significant associations between GADA(+) and beta-cell function. T(+) was observed in 50% of NdxT2D and 60.4% of IGT at baseline, and in 68.4% of NdxT2D and 83.9% of IGT at 12 months. T(+) NdxT2D were observed to have significantly higher fasting glucose (p=0.004), and 2 hour glucose (p=0.0032), but significantly lower steady state C-peptide (sscpep, p=0.007) compared to T(-) NdxT2D. T(+) IGT participants demonstrated lower but not significant (p=0.025) acute (first phase) C-peptide response to glucose (ACPRg) compared to T(-) IGT. With metformin treatment, T(+) participants were observed to have a significantly lower Hemoglobin A1c (HbA1c, p=0.002) and fasting C-peptide (p=0.002) compared to T(-), whereas T(+) treated with liraglutide + metformin had significantly lower sscpep (p=0.010) compared to T(-) participants. In the placebo group, T(+) participants demonstrated significantly lower ACPRg (p=0.001) compared to T(-) participants. In summary, T(+) were found in a large percentage of obese pre-diabetes adults with IGT and in recently diagnosed T2D. Moreover, T(+) were significantly correlated with treatment effects and beta-cell dysfunction. Our results demonstrate that T(+) are an important component in T2D.